Paramutation in Drosophila linked to emergence of a piRNA-producing locus. - de Vanssay, A.; Bougé, A.L.; Boivin, A.; Hermant, C.; Teysset, L.; Delmarre, V.; Antoniewski, C.; Ronsseray, S. (Nature, 2012)
A paramutation is an epigenetic interaction between two alleles of a locus, through which one allele induces a heritable modification in the other allele without modifying the DNA sequence. The paramutated allele itself becomes paramutagenic, that is, capable of epigenetically converting a new paramutable allele. Here we describe a case of paramutation in animals showing long-term transmission over generations. We previously characterized a homology-dependent silencing mechanism referred to as the trans-silencing effect (TSE), involved in P-transposable-element repression in the germ line. We now show that clusters of P-element-derived transgenes that induce strong TSE can convert other homologous transgene clusters incapable of TSE into strong silencers, which transmit the acquired silencing capacity through 50 generations. The paramutation occurs without any need for chromosome pairing between the paramutagenic and the paramutated loci, and is mediated by maternal inheritance of cytoplasm carrying Piwi-interacting RNAs (piRNAs) homologous to the transgenes. The repression capacity of the paramutated locus is abolished by a loss-of-function mutation of the aubergine gene involved in piRNA biogenesis, but not by a loss-of-function mutation of the Dicer-2 gene involved in siRNA production. The paramutated cluster, previously producing barely detectable levels of piRNAs, is converted into a stable, strong piRNA-producing locus by the paramutation and becomes fully paramutagenic itself. Our work provides a genetic model for the emergence of piRNA loci, as well as for RNA-mediated trans-generational repression of transposable elements.